A cross sectional study on the association between new onset of psychiatric symptoms with severity of cognitive impairment in elderly patients - Antony, Jery; Nakulan, Anisha; John, Shiny (International Journal of Research in Medical Sciences, 2019)
Background: Neuropsychiatric impairments play significant roles throughout the course of cognitive decline mainly in older adults with dementia or mild cognitive impairment (MCI). This study was aimed to find the association between psychiatric comorbidities and severity of cognitive impairment in elder patients presented with new onset of Psychiatric Symptoms. Methods: A cross sectional study was done among elder subjects (≥60 years of age) presented with new onset of psychiatric symptoms during one year period. Mini International neuropsychiatric interview and Montreal Cognitive Assessment scale were used for psychiatric diagnosis and severity of cognitive impairment grading, respectively. Association between psychiatric comorbidities and MCI was statistically analyzed. Results: Total 67 subjects were included in the study. Analysis of the psychiatric diagnosis revealed that major depressive episode (52.2%) was the most prevalent psychiatric disorder among the study population followed by Psychotic disorders (23.9%). Generalized anxiety disorder contributed to 19.4% of the total study population. Significant association (p<0.002) was identified between the severity of cognitive impairment and the psychiatric comorbidities. Conclusions: A significant association was identified between the severity of MCI and the psychiatric comorbidities. Major depressive episode was the most prevalent psychiatric disorder followed by psychotic disorders and generalized anxiety disorder.